Employee Performance Analysis with Digital Business Transformation and Organizational Culture as Leveraging Factors - Nasution, Sheila Pratiwi; Sadana, Stefanus M.S. (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Digital business transformation, driven by technologies such as big data analytics, machine learning, and artificial intelligence, plays a crucial role in enhancing organizational competitiveness. However, its success is also significantly influenced by organizational culture, which supports collaboration, open communication, and the acceptance of change. This study aims to investigate the relationship between digital transformation, organizational culture, and employee performance at PT Permodalan Nasional Madani (PNM) Regional Pekanbaru 2. The research found that digital transformation did not significantly impact employee performance, primarily due to the suboptimal implementation of digital initiatives and employees' insufficient digital readiness. On the other hand, organizational culture had a significant positive effect on employee performance. A culture that fosters collaboration, openness, and adaptability was shown to enhance employee motivation and productivity. The study concludes that a strong organizational culture is essential for successfully implementing digital transformation and improving employee performance. Therefore, PNM Pekanbaru 2 should focus on strengthening its organizational culture and provide continuous training to support the effective integration of new technologies, ultimately improving overall performance.